The use of Anticoagulants in Cardiology - Formijne, P (Thrombosis and Haemostasis, 1958)
The possibilities of myocardial infarction-therapy with anticoagulants is discussed. It is important to consider, that although patients with acute myocardial infarction may be in a relatively good condition at home a transfer to the hospital may evidence fatal complications resulting from the traumatic shock inflicted during transport. The benefit of installing early anticoagulant therapy is decisive, but not at the expense of danger to the patient in getting him to a hospital to start treatment. It is suggested that the patient be left at home until he has partially recovered from the acute effects of the coronary occlusion. When doing necropsies on patients with fresh myocardial infarctions treated with anticoagulants, one frequently finds an infiltration of the infarction with blood and ruptures of the ventricle.